The Influence of Product Quality, Content Marketing, and Discount Prices on Purchase Decisions for Roughneck on TikTok - Muhammad Viky Fajar Ardiansyah; Muhammad Rizal yulianto (Economics and Digital Business Review, 2027)
This study aims to analyze the influence of product quality, content marketing, and discount prices on purchasing decisions for Roughneck fashion products on the TikTok application. This study employed a quantitative approach using multiple linear regression analysis. Data were collected through questionnaires distributed to 119 respondents who met the research criteria. The results showed that product quality had a positive and significant effect on purchasing decisions, with a regression coefficient of 0.318, a t-value of 3.721, and a significance value of 0.000. Content marketing also had a positive and significant effect, with a regression coefficient of 0.305, a t-value of 4.177, and a significance value of 0.000. Discount prices had a positive and significant effect, with a regression coefficient of 0.221, a t-value of 2.695, and a significance value of 0.008. Simultaneously, the three independent variables had a significant effect on purchasing decisions, as indicated by an F-value of 150.368 and a significance value of 0.000. The R Square value of 0.797 indicates that 79.7% of the variation in purchasing decisions can be explained by the three independent variables, while the remaining 20.3% is explained by other factors outside the research model